Linking literacy and libraries in global communities - Asselin, Marlene 1949-; Doiron, Ray (Ashgate, 2013)
The authors of this book highlight the emerging role of libraries and community partners in literacy development and provide concrete examples via case studies drawn from global communities, demonstrating how libraries are working to support local literacies. They also suggest recommendations for supporting the critical role for libraries in supporting global literacies. The book will become essential reading for all those interested in literacy and libraries throughout the world.